Madrasah Principal Leadership In Teacher Empowerment : Multi Case Study At Min 9 And Min 14 Blitar - Diyanus Abd Baqi; Akhyak Akhyak; Achmad Patoni (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
This research is inspired by the statement that a good leader must always be able to motivate his subordinates in such a way that in carrying out their duties, teachers will have high work effectiveness and are expected to be able to produce satisfactory results, both for the madrasah and the teachers themselves. The research approach uses qualitative methods. The data collection techniques are participant observation, in-depth interviews and documentation. The research uses individual site and cross-site data analysis. The validity check of data is based on several criteria including: degree of trust, transferability, dependability and confirmability. The results of this research are: 1) The leadership of the madrasah headmaster in raising teachers’ awareness at MIN 9 and MIN 14 Blitar, is carried out by improving the performance of his personnel and by giving awards to subordinates. The head of the madrasah provides a role model and attention, supports welfare, sets a good example, and motivates subordinates. The head of the madrasah supports and appreciates the achievements of his subordinates. The madrasah principal also always tries to take a personal approach by building a good relationship. The setting of a calm and pleasant work atmosphere will increase teacher performance, apart from that, creating a conducive physical environment will increase the motivation of education staff in carrying out their duties. Teacher awareness to increase their ability results of winning national scale literacy competitions. 2) The leadership of the madrasah headmaster in upgrading the capacity of teachers at MIN 9 and MIN 14 Blitar is carried out by ensuring that teachers can professionally carry out their duties by participating in preparing lesson plans, selecting teachers who are competent in guiding students in self-development, providing explanation and motivation to subordinates about how to carry out tasks in the madrasah, informing instructions to subordinates to galvanize their abilities by forming a well-organized work team, arranging a regular learning schedule, and fulfilling school facilities and infrastructure that are adequate and meet standards so that cleanliness and the amenities of the school environment is always maintained. 3) The leadership of the madrasah headmaster in empowering teachers at MIN 9 and MIN 14 Blitar is carried out by inviting subordinates to improve teacher competence, motivating teachers to work, coordinating in terms of work results, always evaluating teacher activities, holding official meetings, providing motivation to teachers during official meetings, being an example by arriving earlier to school and motivating teachers to continue their studies. The madrasah headmaster strives to increase teacher empowerment by giving them duty and authority to oversee superior or extra-curricular programs in the form of arts, religion, scouting and sports.